Advances in the mechanical characterization of ski boots - Pedrone, N. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
Aim of the present work was the consolidation of a sound terminology for the description of ski-boot mechanical behavior, the identification of different internal and external factors that can affect the ski-boot behavior, and the presentation of some preliminary results obtained from experimental tests on five different ski boots (ranging from recreational to racing ski boots) when addressing the effect of temperature, cycle range, and angular velocities and observing the behavior of buckle closure forces.